In the Center of Meaning: Ziarah Tradition in Java - Jamhari Jamhari (Studia Islamika, 2000)
This essay describes the beliefs and practices associated with the notion of ziarah in a single community, that of Bayat, a small district (kecamatan) in Klaten between Yogyakarta and Surakarta. There are some of terms from Bayat in this text, because it is revealing to consider how key terms have been used within their culture of origin. In elucidating ziarah practices and its interpretations, visitors in Bayat refer to the cultural contexts with which they are familiar. The logic of ziarah thus reflects visitor's everyday life experiences. Applying vernacular terms used in Bayat entails taking this cultural context into consideration.DOI: 10.15408/sdi.v7i1.716